Science : Year 9 - Hook, George, 1941- (South Melbourne Nelson Cengage Learning, 1998)
Provides a complete self-study guide for students in the first two years of New Zealand secondary school science. It is designed so that students can understand and recall essential scientific ideas, facts, formulae and skills"--Page 4 of cover.
Include Illustrations and Index
Keywords: Science